1999
DOI: 10.1017/s136898009900021x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and gallbladder disease: a review

Abstract: Objective: Dietary intake has long been looked upon as a potentially modifiable risk factor for gallbladder disease (GBD), here defined as either having gallstones or having had surgery for gallstones. This paper reviews the epidemiological evidence for an association between dietary intake and GBD, focusing on six dietary factors that have received the most attention in studies in this area: energy intake, fatty acids, cholesterol, carbohydrates and fibre, calcium and alcohol. The objectives of this review ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 83 publications
(210 reference statements)
0
11
2
Order By: Relevance
“…The presence of calcium carbonate stones in children as young as 1 year in our series argues against a major dietary cause. Studies of dietary calcium intake in adults have found either no association or an inverse correlation with gallbladder gallstone disease [20]. In our pilot study, we found no link with the calcium carbonate concentration in local drinking water [9].…”
Section: Discussioncontrasting
confidence: 67%
“…The presence of calcium carbonate stones in children as young as 1 year in our series argues against a major dietary cause. Studies of dietary calcium intake in adults have found either no association or an inverse correlation with gallbladder gallstone disease [20]. In our pilot study, we found no link with the calcium carbonate concentration in local drinking water [9].…”
Section: Discussioncontrasting
confidence: 67%
“…Second, they might affect gallbladder function, leading to delayed or incomplete emptying with subsequent bile stasis and dilation of gallbladder, which predisposes to inflammation. The risks of alcohol drinking and smoking on gallbladder cancer were inconsistent in previous studies (Khan et al 1999;Moerman et al 1997;Tseng et al 1999;Zatonski et al 1997). A positive association has been found consistently between gallstones and various measures of obesity (Kono et al 1988;Maclure et al 1989;Pixley et al 1985;Williams and Johnston 1980), with some showing evidence of a dose-response relation (Kono et al 1988;Maclure et al 1989).…”
Section: Discussionmentioning
confidence: 93%
“…For gallbladder carcinoma, gallstones and some structural abnormalities are the known risk factors (Hamilton and Aaltonen 2000; Strom et al 1995;Zatonski et al 1992). The effect of alcohol drinking on gallbladder cancer is controversial Tseng et al 1999). According to the IARC monographs volume 83, smoking is related to liver cancer, but the data on gallbladder cancer are not clear (IARC 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Other than a high caloric intake that leads to obesity, any importance of the dietary content is unclear and difficult to analyze 113-115. Diets specifically high in cholesterol,116 fatty acids, 117 carbohydrates118,119 or legumes120 seem to increase the risk of cholelithiasis.…”
Section: Gallstone Diseasementioning
confidence: 99%